Análise de procedimentos e de aspectos do comportamento estereotipado apresentados na literatura da análise do comportamento - Tufolo, Alice Passos (2018)
For 30 years, stereotyped behavior has been studied by behavior analysts. However, the consensus is that an optimum intervention has no been identified yet. Taking that into consideration, the present study intended to assess: a) how stereotyped behavior has been described in the literature; b) possible causes for stereotypy; c) successful interventions in the field; and d) critically appraise those interventions. To achieve these goals, a review was conducted, crossing seven search terma across four databases. In total, 31 studies were selected. All of these studies, had the aim to reduce the frequency of stereotyped responses. Results analysis showed that: 1) there’s no consensus in regard to the definition of stereotyped behavior; 2) there’s also no consensus in regard to the best way to intervene in stereotyped behaviors; 3) analysed studies show little consistency with regard to the conducting functional analysis, and often interventions are designed without a base on the behavior function; 4) no study conducted all of the following: generalization, follow up and social validity appraisal and; 5) most procedures utilized aversive techniques in their interventions. As such, we note a need to better define study objects, experimental control in such studies and the relation between applied research and subsequente intervention